2018
DOI: 10.1159/000493582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cellulose Powder on Human Nasal Epithelial Cell Activity and Ciliary Beat Frequency

Abstract: Background: Cellulose powder (CP) has been reported as a safe and effective complementary treatment for allergic rhinitis (AR). Currently, CP has gained increasing application for clinical management worldwide, particularly in China. However, studies focusing on the effect of CP on normal human nasal epithelial cells (hNECs) and ciliary function are lacking. Here, we aimed to explore the adverse effects of CP on the activity and ciliary function of hNECs. Methods: We biopsied ethmoid sinus or middle turbinate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…3 A single ex-vivo study suggests that higher doses of cellulose powder may have a negative effect on the viability of the nasal epithelium and on its ciliary beat frequency. 20 The data of this experimental study hint at a possible negative effect only with the highest concentration of pHPMC. However, these concentrations were just experimental and would never be reached clinically.…”
Section: Discussionmentioning
confidence: 65%
“…3 A single ex-vivo study suggests that higher doses of cellulose powder may have a negative effect on the viability of the nasal epithelium and on its ciliary beat frequency. 20 The data of this experimental study hint at a possible negative effect only with the highest concentration of pHPMC. However, these concentrations were just experimental and would never be reached clinically.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have shown that the clinically used concentrations of adrenaline and lidocaine do not affect the CBF of epithelial cells collected using the nasal brush. 16,17 The nasal scraping spoon used in this current study is metallic, inexpensive, sterilizable and reusable; and allows the collection of enough high-purity cells. The fifth generation of nasal cells collected using the nasal scraping spoon had an immunofluorescent appearance that was consistent with cultured primary NEC and all cells were positive for CK-18 staining (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…We also confirmed the presence of epithelial-derived exosomes by isolating hNECs from primary tissues. In our previous result, we showed that the cultured primary epithelial cells contained high percentage of epithelial cells (>95%) [25] which was suitable for downstream studies of epithelial derived exosomes. The hNECs were cultured for 2 weeks, followed by harvesting of the cell medium.…”
Section: Exosomes In the Nlf And Hnecs Of Patients In The Healthy Controls Crswnp And Crswnp With Asthma Groupsmentioning
confidence: 99%